Organoleptic Value and Cholesterol Content of Shredded Meat of Rejected Layers Based on Immersion Level of Lime Juice (Citrus aurantifolia S.) - Bulkaini Bulkaini; Djoko Kisworo; M. Alfatih; Akhyar Sutaryono; Maskur Maskur; I K Sumadi (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
The production of shredded meat is an innovation to improve the structure of rejected layers of meat into processed products that are tender and low in cholesterol. This study aims to determine the effect of the immersion level of lime juice (Citrus aurantifolia S.). On the organoleptic value and cholesterol of shredded hens of rejected layers. The study was carried out using a randomized block design in the same direction with four treatments and tree replications, namely P0 = meat without soaking in Citrus aurantifolia S liquid; P1= meat soaked in 200 ml of Citrus aurantifolia S liquid, P2= meat soaked in 250 ml of Citrus aurantifolia S liquid and P3= meat soaked in 300 ml of Citrus aurantifolia S liquid. The research data were analyzed using the Analysis of Variance and continued with Duncan's Multiple Range Test using the SPSS 25 program. The results showed that soaking meat in Citrus aurantifolia S liquid in the production of shredded culled laying hens had no significant effect (p>0.05) on organoleptic quality (aroma, tenderness, taste, and acceptance), significantly (p<0.05) can improve the shredded structure according to the Indonesian National Standard (SNI: 1995). Conclusion: Soaking culled laying hens in Citrus aurantifolia S. liquid at a level of 200-300 ml of meat weight can produce shredded meat with a pleasant aroma, tender, tasty, soft, and acceptable to panelists with normal cholesterol levels, namely 10.00 - 46.66 mg/dl.